Comparison of Radio- and Phototoxicity in Association with an Enhancing Effect of the Photosensitizers Psoralen, Trioxsalen and Ortho-Iodo-Hoechst33258 on FaDu, PC-3, 4T1 and B16-F10 Cells - Katja Tietze; Florian Brandt; Kerstin Wetzig; Lisa Hübinger; Marc Pretze; Ralph Alexander Bundschuh; Jörg Kotzerke (Biomedicines)
Background: Energy delivered at different wavelengths causes different types of damage to DNA. Methods: PC-3, FaDu, 4T1 and B16-F10 cells were irradiated with different wavelengths of ultraviolet light (UVA/UVC) and ionizing radiation (X-ray). Furthermore, different photosensitizers (ortho-iodo-Hoechst33258/psoralen/trioxsalen) were tested for their amplifying effect. Survival fraction and damage analysis using the <semantics>γ</semantics>H2A.X assay (double-strand breaks) and the ELISA assay (cyclobutane pyrimidine dimers) were compared. Results: The PC-3 cells were found to be the most sensitive cells to the treatment strategies used. FaDu and PC-3 showed a strong sensitivity to UVA. Analysis of the damage showed that the cell lines exhibited different sensitivities. Conclusions: Thus, an enhancing effect of photosensitizers (PS) in combination with UVA could be demonstrated in some cases. However, this is cell- and dose-dependent.